Penyimpangan Prinsip Kesantunan Pada Teks Pengumuman Karya Siswa Kelas VII SMP Muhammadiyah 4 Sambi Tahun Ajaran 2015/2016: Tinjauan Pragmatik - Hartiningrum, Wahyu; Dra. Atiqa Sabardila, M. Hum., Dra. Atiqa Sabardila, M. Hum (2016)
This research has two aim, as follow (1) Identifying forms of deviation linguistic politeness in the text of announcement made by students of class VII SMP Muhammadiyah 4 Sambi (2) Describe the correct form of politeness to deviations linguistic politeness in the text of announcement made by students of VII grade SMP Muhammadiyah 4 Sambi. This research is a qualitative research. Objects that exist in this research is a deviation politeness on the text of announcement made by students of VII grade. This research data such as words and sentences that contain the deviation politeness on the text of announcement made by students of VII grade SMP Muhammadiyah 4 Sambi. Data collection techniques are observe attentively methods and take notes, record and documentation. Authenticity technique of data in this research use triangulation technique. Data analysis techniques use padan intralingual method. This research results indicate that form of impoliteness speaking at announcement text made by students of VII grade SMP Muhammadiyah 4 Sambi Boyolali, include Cost-benefit scale or of losses and gains scale; Optionalityscale, Indirecnessscale, Authorityscale, dan socialdistance. Impoliteness speaking on the text of announcement made by students in terms of Optionalityscale amounts to thirteen data. Impoliteness speaking on the text of announcement made by students in terms form Authorityscale amounts to one data